Chemically reacting ionized radiative fluid flow through an impulsively started vertical plate with induced magnetic field - Ahmed, Tanvir; Alam, Mahmud; Ferdows, Mohammad; Tzirtzilakis, Efstratios (Zielona Góra: Uniwersytet Zielonogórski)
Numerical studies have been performed to examine the chemically reacting ionized fluid flow through a vertical plate with induced magnetic field. This study is performed for the cooling problem. To obtain the non-dimensional non-similar momentum, the induced magnetic field, energy and concentration equations, usual non-dimensional variables have been used.
Keywords: boundary layer; radiative flow; strong magnetic field; ionized gas; flow fields